The competitiveness of Portugal: Views from the market - Silva, G.; Pereira, L. F.; Carvalho, J. C.; Vinhas da Silva, R.; Simões, A. (Competitiveness Review, 2024)
Purpose - This study aims to conduct a pertinent assessment of the concept of business competitiveness and how Portugal can progress in that field, for the sake of becoming a more sustainable and wealth-creator economy. Design/methodology/approach - The research was elaborated with 65 in-depth interviews with expert persons from the Portuguese business ecosystem, who were asked to reflect on the state of the economy and competitiveness of the country. Findings - There is much room for improvement in almost all areas of activity, in particular by promoting an innovative, value-adding and exporting private sector and a lighter and more efficient public sector. The conclusions point to modernisation of the Portuguese economy as a way of making it more competitive in a highly competitive and demanding global scenario. Originality/value - To the best of the authors’ knowledge, it is the first time that a reflection with experts of the local Portuguese economy has been carried out, especially after a difficult period of COVID.